2017
DOI: 10.1615/critreveukaryotgeneexpr.2017018953
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis C Infection in Pakistan: Current Estimate and Major Risk Factors

Abstract: In Pakistan, hepatitis C virus (HCV) is a major healthcare problem, with acute and chronic infections responsible for liver damage, cirrhosis, and hepatocellular carcinoma. Under the Human Development Index of the United Nations, Pakistan is ranked 134th of 174 countries due to its poor educational and health standards. This study was designed to study HCV and its genotype prevalence in different cities and provinces of Pakistan and describe the major routes of HCV transmission. Literature searches were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 0 publications
4
39
0
1
Order By: Relevance
“…In the current study, the most common risk factors associated with HCV infection was injection use, intravenous infusion, and skin piercing. These findings are in concordance with other studies reported from Pakistan and demonstrate the importance of proper public awareness programs to reduce the prevalence of HCV infection in Pakistan (25)(26)(27). In a recent study carried out in Faisalabad, Pakistan, the most prominent risk factor was injecting drug use observed in 51% of HCV patients (27).…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the most common risk factors associated with HCV infection was injection use, intravenous infusion, and skin piercing. These findings are in concordance with other studies reported from Pakistan and demonstrate the importance of proper public awareness programs to reduce the prevalence of HCV infection in Pakistan (25)(26)(27). In a recent study carried out in Faisalabad, Pakistan, the most prominent risk factor was injecting drug use observed in 51% of HCV patients (27).…”
Section: Discussionsupporting
confidence: 90%
“…Liver disease develops slowly over numerous decades in most of the patients. In Pakistan, chronic HCV is a foremost healthcare challenge resulting liver inflammation, tissue scarring, liver cirrhosis and HCC without treatment [40,41]. Many studies conducted to determine the relationship between severity of biochemical abnormalities and serum viral load and they have produced contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, implementation of some preventive measures, such as raising awareness in the general population and healthcare system about the routes of HCV transmission, requires knowledge about HCV risk factors. Due to the inaccessibility of vaccines for HCV prevention, researchers have focused on the regular analysis of HCV risk factors in different populations to clarify the current routes of HCV transmission around the world (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Overall, the significance of HCV risk factors varies in different populations and regions.…”
Section: Introductionmentioning
confidence: 99%